The Effect of Forgiveness and Self-Acceptance on Students Resilience through Social Support as the Mediator - Putri, Rieny Kharisma; Puji Sugiharto, Dwi Yuwono; Awalya, Awalya (Universitas Negeri Semarang, 2022)
Resilience is important for individuals to rise in facing risky and stressful situation. It is done by using defensive ability as well as positive and flexible adaptation towards the problems faced. This research identified and analyzed the effect of forgiveness and self-acceptance on resilience through social support as the mediating variable. It was correlational research with ex post facto design which involved 369 students as the population and 160 as the sample selected using random sampling technique. Their data were collected using resilience scale, forgiveness scale, self-acceptance scale, and social support scale. After that, the collected data were analyzed using SEM method on AMOS software. Findings showed an indirect effect of social support on the influence of forgiveness and self-acceptance on resilience. Finally, this research can be a basis for the future research.